Pre-testing erroneous text-based documents: Logging end-user activities - Nagy, Keve; Csernoch, Mária (Frontiers in Education, 2023)
An extremely high number of erroneous text-based documents are in circulation, being multiplied, serving as samples both in the office world and in education. Creating, editing, and modifying these documents generates a serious financial loss when both human and machine resources are considered. Our research team developed an application and a testing method for building up an objective measurement system, in order to see the rate of loss in the handling of erroneous documents. In our pre-testing period, it was found that minimal modifications require five times as much human and machine resources in a text burdened with layout errors as in its properly formatted version. Further testing is required to find how demanding longer texts and more serious modifications are, but it is already obvious that erroneous text-editing and the lack of fundamental computational thinking skills use up our resources senselessly.